The Heroine’s Unconscious Journey towards Matriarchy in Radcliffe’s A Sicilian Romance - Fatima Yahyapoor (International Journal of Practical and Pedagogical Issues in English Education)
The role that the parents play in the psychology of a child is indispensable. They are the two human beings that the child comes into contact with and looks up to them in almost everything. The Jungian psychology has tried to investigate the roots of father and mother in archetypal psychoanalysis and their relationship to childhood. Psychoanalytical readings of Radcliffe categorize her in female gothic and see her as a proto-feminist. While they are right about her search for a lost matriarchy, they ignore her endings in marriage. Radcliffe’s A Sicilian Romance is filled with symbolism and symbolic elements. The mother-daughter relation including both rivalry and friendship is central to the novel. Sometimes the heroine antagonizes certain father figures and mother figures. At other times she looks for and cherishes other father and mother figures. The heroine' double attitude towards her parents resembles the double faces of father and mother archetypes. Her running from tyrant Patriarch and Matriarch is toward a new benevolent Matriarch who is later replaced by a chivalrous hero figure. The hero substitutes the father and plays the role of a husband who shows features of a chivalric manhood in a long-gone past. In the end While Radcliffean heroine in A Sicilian Romance is looking unconsciously for her mother and therefore the lost Matriarchy, she consciously accepts an ideal Patriarchy.